Study on effect of abs control system to the vehicle dynamic behavior during braking on various speed and road condition - Muhamad Zulhilmi, Ismail (2021)
The vehicle safety system is divided into two groups that are passive safety and active safety system. While a passive safety system’s purpose is to protect the occupant during an accident, an active safety system’s goal is to enable the vehicle to be controlled to avoid any collision. The passive safety system is a seatbelt, airbag, headrest, etc. Anti-lock Braking System (ABS) is one of many systems under the active safety system, a basic skid control system that can prevent the tire from locking up and enable the vehicle to steer during braking. Another active system is Forward Collision Warning (FCW), Electronic Stability Control (ESC), etc. Even with an active safety system, especially during emergency braking, the vehicle dynamic behavior may change abruptly, which can cause the vehicle to become unstable. The incident may be worse during emergency braking on the wet road condition. This study focuses on analyzing the vehicle dynamic behavior during emergency braking without and with ABS enabled in the system on dry and wet road conditions. The analysis of this study is divided into three phases; to investigate the vehicle dynamic behavior of the UMP test car (Proton Persona) during the braking experiment without ABS, development of the mathematical model of the vehicle and validation with the experimental result, and analyses of the simulation model with implementation of ABS. From the experimental results, on dry road conditions, all experiments conducted from an initial speed of 30 km/h, 50 km/h, and 60 km/h show no locking up occurred. While on wet road conditions, the lock-up condition is shown at front tires starting from the experiment at an initial speed of 50 km/h and 60 km/h. From experimental data, the mathematical model is simulated inside Matlab Simulink, and the model validation using RMSE is all under 10 % for vehicle speed, tire speed, stopping distance and slip ratio. With the addition of ABS inside the model, the simulation was repeated. Only on wet road condition is re-performed as on dry road condition there is no lock-up occur. With ABS enabled in the simulation, it is shown that the speed of all tires decreased gradually and no lock-up occurred. Thus, showing the modelling stay or lower than the optimum range of slip ratio used in the ABS. Additionally, the friction coefficient between the tire and the road was high, meaning the vehicle could be steered properly during braking. Data also shows shorter in both stopping time and stopping distance. The vertical forces also reduce periodically, showing the increase of vehicle stability. Furthermore, with the development of the mathematical model in this research, various ABS algorithms to improve the effectiveness of ABS on the vehicle can be done in future studies.